The role of faith in developing community civilization - Engku Ahmad Zaki, Engku Alwi; Roose Nilawati, Subki; Nor Aini, Abu Bakar (Mediterranean Centre of Social and Educational Research, 2014)
This paper hopes to highlight the role of faith in ensuring social stability with reference to Al-Quran and to prove that faith is the determining agent of social stability of a community civilization. Thus, all parties responsible in developing the human capital and social stability towards achieving an excellent community civilization need to give emphasis on the aspects of faith.